Slum Politics in Jakarta: Comparison of Slum Areas in Karet Tengsin and Guji Baru based on Urban Social Movement Theory - Febriali Sahl, Dafiq; Nurisha Kitana (CIC Lembaga Riset dan Konsultan Sosial, 2024)
The city is a complex reality that reflects the struggle for political, economic, and cultural spaces and resources amidst limitations and contingencies in achieving justice for all city residents. The concepts of the Right to the City and Urban Social Movements, as explored in urban political literature, serve as an exploratory framework for this qualitative-descriptive research. They help to understand the struggles for the right to the city through urban social movements in Karet Tengsin and Kampung Guji Baru, Jakarta. This study employs both primary and secondary data collection methods. Primary data were gathered through interviews with three key informants: two activists from Tim 9 in Karet Tengsin and one activist from Serikat Perjuangan Rakyat Indonesia (SPRI) in Kampung Guji Baru. These interviews were further supported by direct observation conducted over approximately one month in both areas. Secondary data, including literature from books, scientific journals, and media reports, complement the analysis and provide insights into the empirical realities of urban social movements by slum residents in Jakarta. The findings demonstrate distinct differences in the models, types, and demands of struggles for the right to the city as exhibited by Tim 9 in Karet Tengsin and SPRI in Kampung Guji Baru. Moreover, the empirical evidence descriptively concludes that the Jakarta government has yet to fully realize the right to the city, particularly in providing access to adequate housing and sustainable livelihoods (collective consumption).